Effects of low crude protein, amino acid fortified diets and neutral detergent fiber on finishing pig performance - Soto Gonzalez, Jose Alfredo (Kansas State University, 2018)
Eleven experiments using 5,434 growing-finishing pigs were performed in addition to the development of a model to predict dietary NE that yields the greatest economic benefit. Two experiments were conducted to determine the effect of dietary phytogenics on growth and carcass performance of growing-finishing pigs. The addition of the combination of two phytogenics products (EOM 1+2) to diets improved ADFI, HCW, and carcass ADG. However, there was no evidence for treatment differences for growth or carcass performance in a second study. Two experiments were conducted to determine the effects of feeding high SID Trp:Lys ratios with and without Ractopamine HCl (RAC) on growth and carcass characteristics of finishing pigs. In Exp. 1, whereas increasing SID Trp:Lys ratio above 20% improved growth and carcass performance when diets contained RAC, pigs fed SID Trp:Lys ratios above 20% in diets without RAC had reduced growth and carcass performance. Contrary in Exp. 2, pigs fed increasing SID Trp:Lys in diet containing RAC did not provide further performance benefits. Three experiments were conducted to determine the optimum dietary SID Lys and CP concentrations in finishing pigs over 100 kg. The SID Lys requirement to obtain 100% of maximum response was 0.55 to 0.63% depending on the response variable. Growth and carcass performance was maximized in diets containing at least 12% dietary CP. Four experiments were conducted to determine the effects of SBM concentration and whether dEB, choline, or K are the reasons that performance is reduced when pigs over 100 kg BW are fed low CP diets. Performance was reduced as SBM concentration was reduced in the diet. Choline, K, and dEB do not appear to be the reason that performance is reduced when SBM concentration is decreased in low CP diets fed to pigs over 100 kg BW. A Microsoft Excel®-based model to predict the value of dietary NE that yields the greatest economic return to the production system was developed. Furthermore, a meta-analysis was conducted to incorporate the impact of NDF on carcass yield in the model.
Keywords: Amino acids; Crude protein; Finishing pigs; Net energy; Neutral detergent fiber; Soybean meal